2021
DOI: 10.1038/s41598-021-84282-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological adaptability and population growth tolerance characteristics of Carex cinerascens in response to water level changes in Poyang Lake, China

Abstract: Water level conditions are the key factors that affect the growth and distribution of wetland plants. Using Carex cinerascens (C. cinerascens) as the study species, we employ indoor simulations and field surveys. Our results show that C. cinerascens can adapt to rhythmic changes in the water level through different adaptation strategies. Compared to that of the control group, plant growth was better with a 0–0.4 cm/d water level rate, and plant growth was in the 42–56 cm range to that a 1.0–1.4 cm/d water leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…PYL and DTL wetlands are the most important habitats and migration routes for migratory birds in East Asia, and play an essential role in global biodiversity conservation (Qu et al, 2020;Xiao et al, 2022;Yao et al, 2021). Previous studies have shown that the EDS has caused changes in landscape patterns and HS of migratory birds in PYL and DTL wetlands (Wu et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…PYL and DTL wetlands are the most important habitats and migration routes for migratory birds in East Asia, and play an essential role in global biodiversity conservation (Qu et al, 2020;Xiao et al, 2022;Yao et al, 2021). Previous studies have shown that the EDS has caused changes in landscape patterns and HS of migratory birds in PYL and DTL wetlands (Wu et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between water level change and plant population characteristics, species diversity and life history have been studied. Researches showed that fluctuation and its frequency are important factors affecting the growth, reproduction, and population distribution of wetland plants (Gattringer et al, 2018;Yao et al, 2021). Water fluctuation increased number of shoot nodes and shoot length of the communities, and may increase the vegetative spread of submerged macrophyte communities (Wang et al, 2016), and biomass accumulation in roots rather than in shoots and the ability to asexually propagate were important for the survival of these species during water fluctuation (Wei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors (temperature, humidity, rainfall, wind speed, water and soil) affect every aspect of plant growth and development (Butto et al, 2021). Plants adopt different strategies for survival and growth under the fluctuated environmental conditions (Yao et al, 2021). The wood (secondary xylem), an outcome of the activity of vascular cambium (radial growth) and leaf production pattern is greatly influenced by the environmental factors of the habitat (Qaderi et al, 2019).…”
Section: Candd)mentioning
confidence: 99%